SEASONAL VARIABILITY OF THE SURFACE WATER CIRCULATION IN THE NORTHERN JAPAN SEA BY DATA OF DRIFTING BUOYS - S. N. Taranova; G. I. Yurasov; I. A. Zhabin (Известия ТИНРО)
Data of observations on drifters in 1988–2015 are used to study seasonal variability of the surface water circulation in the Japan Sea. The well-known circulation patterns are observed, as the Tsushima Current, the East-Korean Current, the Primorye Current, and the northern cyclonic gyre. In the fall season (October), the main features of the mean flow are a very strong inflow through the Korean/Tsushima Strait and the intensive Tsushima Current and East-Korean Current. In winter (January), the cyclonic gyre over the norther basin and the Primorye Current along Primorye coast are strengthened. These seasonal changes of the flow field are presumably caused by monsoon winds variation. In spring (April) and summer (July), the water circulation is generally weakened; one of important patterns of the summer circulation in the northern Japan Sea is the westward branch of the Tsushima Current toward Primorye coast.